Cosmopolitan Da'wah as a Social Response to the Phenomenon of Țarīqah Gairu Mu'tabarah in Indonesia - Risa Alivia; Kombang Tua Siregar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article examines the concept of cosmopolitan da‘wah as a social response to the phenomenon of ṭarīqah gairu mu‘tabarah ‘ṣūfī orders’ in Indonesia through a qualitative library research approach. Data were collected systematically from official documents of the Ministry of Religious Affairs, fatwas of the Indonesian Ulama Council, academic works on sufism, and international journal articles, and were analyzed using content and thematic analysis. Employing Vertovec and Cohen’s theory of cosmopolitanism, the study argues that the existence of gairu mu‘tabarah orders cannot be reduced merely to questions of sanad legitimacy but should also be understood as expressions of spiritual plurality within contemporary muslim society. The findings demonstrate that the six dimensions of cosmopolitanism. Sociocultural conditions, worldview, transnational political projects, identity recognition, dispositional orientations, and practices, provide an analytical framework that positions cosmopolitan da‘wah as a means of accommodating ṣūfī diversity, strengthening social cohesion, and fostering an inclusive, moderate, and peaceful spiritual space.